Biological Roles and Therapeutic Applications of IDH2 Mutations in Human Cancer - Guo, Jinxiu; Zhang, Ruyue; Yang, Zhe; Duan, Zhenfeng; Yin, Detao; Zhou, Yubing (Frontiers in Oncology, 2021)
Isocitrate dehydrogenase (IDH) is a key metabolic enzyme catalyzing the interconversion of isocitrate to α-ketoglutarate (α-KG). Mutations in IDH lead to loss of normal enzymatic activity and gain of neomorphic activity that irreversibly converts α-KG to 2-hydroxyglutarate (2-HG), which can competitively inhibit a-KG-dependent enzymes, subsequently induces cell metabolic reprograming, inhibits cell differentiation, and initiates cell tumorigenesis. Encouragingly, this phenomenon can be reversed by specific small molecule inhibitors of IDH mutation. At present, small molecular inhibitors of IDH1 and IDH2 mutant have been developed, and promising progress has been made in preclinical and clinical development, showing encouraging results in patients with IDH2 mutant cancers. This review will focus on the biological roles of IDH2 mutation in tumorigenesis, and provide a proof-of-principle for the development and application of IDH2 mutant inhibitors for human cancer treatment.